Effectiveness of the Family Heart Talk Communication Tool in Improving Family Member Screening for Dilated Cardiomyopathy: Results of a Randomized Trial. Issue 17 (20th March 2023) - Kinnamon, Daniel D.; Jordan, Elizabeth; Haas, Garrie J.; Hofmeyer, Mark; Kransdorf, Evan; Ewald, Gregory A.; Morris, Alanna A.; Owens, Anjali; Lowes, Brian; Stoller, Douglas; Tang, W.H. Wilson; Garg, Sonia; et al.
Abstract : Background: Managing disease risk among first-degree relatives of probands diagnosed with a heritable disease is central to precision medicine. A critical component is often clinical screening, which is particularly important for conditions like dilated cardiomyopathy (DCM) that remain asymptomatic until severe disease develops. Nonetheless, probands are frequently ill-equipped to disseminate genetic risk information that motivates at-risk relatives to complete recommended clinical screening. An easily implemented remedy for this key issue has been elusive. Methods: The DCM Precision Medicine Study developed Family Heart Talk, a booklet designed to help probands with DCM communicate genetic risk and the need for cardiovascular screening to their relatives. The effectiveness of the Family Heart Talk booklet in increasing cardiovascular clinical screening uptake among first-degree relatives was assessed in a multicenter, open-label, cluster-randomized, controlled trial. The primary outcome measured in eligible first-degree relatives was completion of screening initiated within 12 months after proband enrollment. Because probands randomized to the intervention received the booklet at the enrollment visit, eligible first-degree relatives were limited to those who were alive the day after proband enrollment and not enrolled on the same day as the proband. Results: Between June 2016 and March 2020, 1241 probands were randomized (1:1) to receive Family Heart Talk (n=621) or not (n=620) within strata defined by site and self-identified race/ethnicity (non-Hispanic Black, non-Hispanic White, or Hispanic). Final analyses included 550 families (n=2230 eligible first-degree relatives) in the Family Heart Talk arm and 561 (n=2416) in the control arm. A higher percentage of eligible first-degree relatives completed screening in the Family Heart Talk arm (19.5% versus 16.0%), and the odds of screening completion among these first-degree relatives were higher in the Family Heart Talk arm after adjustment for proband randomization stratum, sex, and age quartile (odds ratio, 1.30 [1-sided 95% CI, 1.08–∞]). A prespecified subgroup analysis did not find evidence of heterogeneity in the adjusted intervention odds ratio across race/ethnicity strata ( P =0.90). Conclusions: Family Heart Talk, a booklet that can be provided to patients with DCM by clinicians with minimal additional time investment, was effective in increasing cardiovascular clinical screening among first-degree relatives of these patients. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03037632.